2022-RA-1310-ESGO Cost-effectiveness of unselected multigene germline and somatic genetic testing for epithelial ovarian cancer. (20th October 2022) - Sun, Li; Sobocan, Monika; Rodriguez, Isabel V; Wei, Xia; Kalra, Ashwin; Oxley, Samuel; Sideris, Michail; Morgan, Robert D; Chandrasekaran, Dhivya; Rust, Kelly; Spiliopoulou, Pavlina; Miller, Rowan E; et al.
Abstract : Introduction/Background: Parallel panel-germline and somatic-testing in all women with ovarian-cancer (OC) identifies more pathogenic-variants (PV) benefitting from poly-ADP-ribose (PARP) inhibitor (PARP-i) therapy, and unaffected PV-relatives for precision prevention. This study aims to estimate cost-effectiveness and population impact of parallel panel-germline and somatic BRCA -testing all OC-patients incorporating PARP-i therapy, compared with family-history (FH)/clinical-criteria based germline BRCA -testing in UK and USA health-systems. Methodology: Microsimulation cost-effectiveness modelling using data from 2, 391 unselected population-based OC-patients recruited to UK (n=1, 483) and USA (n=908) research studies. The lifetime costs-&-effects of BRCA1/BRCA2/RAD51C/RAD51D/BRIP1 germline-testing and somatic BRCA1/BRCA2- testing in all OC-cases ( BRCA -mutated patients undergo PARP-i therapy) (Strategy-A), was compared with FH/clinical-criteria based germline BRCA -testing (Strategy-B). Unaffected relatives with germline BRCA1/BRCA2/RAD51C/RAD51D/BRIP1 PVs identified through cascade-testing undergo relevant OC and breast-cancer (BC) risk-reduction interventions (risk-reducing salpingo-oophorectomy, MRI/mammography, chemoprevention or risk-reducing-mastectomy). We also evaluated cost-effectiveness of germline-panel testing alone (without PARP-i therapy). A lifetime horizon with payer/societal perspectives, along-with probabilistic and one-way sensitivity-analyses are presented. Incremental-cost-effectiveness-ratio (ICER): incremental-cost per quality-adjusted-life-year (QALY) gained, was compared to £30, 000/QALY(UK) and $100, 000/QALY(USA) thresholds. OC-incidence, BC-incidence and prevented deaths were estimated. Results: Compared with clinical-criteria/FH-based BRCA -testing, BRCA1/BRCA2/RAD51C/RAD51D/BRIP1 germline-testing and BRCA1/BRCA2 somatic-testing all OC patients incorporating PARP-i therapy demonstrates UK-ICERs (payer-perspective=£42, 433/QALY; societal-perspective=£41, 622/QALY) and USA-ICERs (payer-perspective=$145, 071/QALY; societal-perspective=$144, 564/QALY) are higher than UK/NICE and USA cost-effectiveness thresholds. Strategy-A becomes cost-effective if PARP-i costs fall by 32% (UK) or 33% (USA), or overall-survival (OS) with PARP-i reaches HR=0.28. Unselected panel-germline testing (without PARP-i therapy) is extremely cost-effective from payer-perspective (UK-ICER=£11, 291/QALY; USA-ICER=$68, 808/QALY); and societal-perspectives (UK-ICER=£6, 923/QALY; USA-ICER=$65, 786/QALY). One year's unselected testing could prevent 199 BC/OC-cases and 236 deaths in UK-women; and 523 BC/OC-cases and 581 deaths in USA-women. Conclusion: Unselected panel-germline and somatic BRCA -testing is currently not cost-effective but becomes cost-effective if PARP-i costs fall by 32%-33% or OS reaches HR=0.28. Regarding germline-testing, unselected panel-germline testing is highly cost-effective and should replace BRCA -testing alone.